Polydnavirus Symbiont Detected from Calyx TissuesWasps of Three Lepidopteran Cabbage Pests - ENDANG SRI RATNA; DAMAYANTI BUCHORI; TEGUH SANTOSO (Microbiology Indonesia, 2011)
Parasitoid wasps are a potent biological control agent in the field. The successful of parasitism are determined by several factors, among them by the presence of polydnavirus (PDV) symbiont that could break down the immunity mechanism of its host.We explored the existence of PDV on wasps , Snellenius manilae, Cotesia sp., and  Diadegma semiclausum a group of parasitoid on cabbage pests in Indonesia. Morphological study of PDV was done by preparing ultrasectioned calyx tissues and negative stained of extracted calyx fluid of adult parasitoids. Virogenic stroma resulted from differentiated calyxepithelial cells appeared on all three wasps. Bracovirus and ichnovirus were detected from the calyx tissues of S. manila and D. semiclausum . The electron dense materials of PDV were distributed within nucleus and vacuolated cytoplasm of calyx cells, calyx lumen and on the surface of eggs wasps. PDVs particles were also shown in the extracted calyx fluid of Cotesia sp.